Pediatric Anesthesia Specialty Societies and Multi-Institutional Collaborations - Camila B. Walters; James M. Kynes; Srijaya K. Reddy; Christy J. Crockett; Hannah K. Lovejoy; Amanda N. Lorinc (MDPI AG, 2020)
Pediatric anesthesiology is a subspecialty of anesthesiology that deals with the high-risk pediatric population. The specialty has made significant advancement in large collaborative efforts to study and increase patient safety, including the creation of international societies, a dedicated journal, special committees and interest groups, and multi-institution databases for research and quality improvement. Readily available resources were created to help with the education of future pediatric anesthesiologists as well as continuing medical education. Conclusions: Specialty societies and collaborations in pediatric anesthesia are crucial for continuous improvement in the care of children. They promote research, education, quality improvement, and advocacy at the local, national, and international level.